2022
DOI: 10.1017/jns.2022.14
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body weight in response to pecan-enriched diets with and without substitution instructions: a randomised, controlled trial

Abstract: Substantial evidence suggests that regular tree nut consumption does not lead to changes in body weight (BW). However, these studies used a variety of dietary substitution instructions which may confound the interpretation of prior BW outcomes. The purpose of the present study was to examine the impact of daily pecan consumption, with or without isocaloric substitution instructions, on BW and composition. This was an 8-week randomised, controlled trial with three treatments: a nut-free control group (n 32) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…A recommended nut consumption for cardiovascular prevention is 1.5 ounces per day (∼42.5 g) [ [47] , [48] , [49] ]. A concern about tree nuts is that they are high in energy and total fat, [ 50 ] yet clinical trials have demonstrated that not all energy present in tree nuts is bioavailable [ [51] , [52] , [53] , [54] , [55] ]. Moreover, a systematic review and meta-analysis of prospective cohorts and randomized controlled trials demonstrate that nut consumption does not lead to increased weight or measures of adiposity [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recommended nut consumption for cardiovascular prevention is 1.5 ounces per day (∼42.5 g) [ [47] , [48] , [49] ]. A concern about tree nuts is that they are high in energy and total fat, [ 50 ] yet clinical trials have demonstrated that not all energy present in tree nuts is bioavailable [ [51] , [52] , [53] , [54] , [55] ]. Moreover, a systematic review and meta-analysis of prospective cohorts and randomized controlled trials demonstrate that nut consumption does not lead to increased weight or measures of adiposity [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reasons for the absence of weight gain ensuing nut consumption have been considered. First, eating nuts increases satiety due to their high fat and fibre contents, with the suppression of hunger and promotion of fullness [1,9,45]. Second, nut ingestion entails impaired energy absorption efficiency in the gastrointestinal tract due to a reduced bioaccessibility of fat encased in nut cell walls, plus an increased binding of fatty acids in the gut by nut fibre, with attending increases in fecal fat losses [1,9].…”
Section: Discussionmentioning
confidence: 99%